Mazhab Menjaga Kemurnian Ajaran Islam - Syamsul Maarif; Imron Choeri (Faculty of Sharia and Law Universitas Islam Nahdlatul Ulama, 2023)
The model of practicing Islamic teachings carried out by the majority of Muslim communities in the world is by following the pattern of madhab. Madhab groups tend to have a wasatiyah attitude in their daily lives. However, there are some Muslim communities in the world who implement Islamic teachings without referring to the pattern of madhab (anti-mazhab).. The truth belongs only to one's own group. Therefore, the attitude of this anti-madhab group tends to be rigid in religion. However, the facts say that the majority of Muslims in parts of the world still faithfully adhere to the teachings of the four schools of Fiqh (Hanafi, Maliki, Syafi'i and Hanbali) in implementing Islamic teachings. At this point, it would certainly be interesting to study in more depth what the true benefits of following the four schools of thought (Hanafi, Maliki, Syafi'i and Hanbali) are in Islam. Madhab should be understood as a manhaj for understanding the Koran and Sunnah. Madhab is a continuation of the Islamic teachings that the Prophet conveyed to his friends to reach the next generation. Therefore, practicing madhhab is necessary and valid throughout time to know the purity of the teachings of the Islamic religion.